The effect of instagram ads and hedonic shopping motivation on impulse buying through positive emotion (study on management students class of 2018-2020) - Ahmad Fahri; Citra Savitri; Syifa Pramudita Fadila (Trigin Publisher, 2022)
Current buying behavior has changed, where many people make unplanned purchases. Many people who make purchases of a particular product or brand because of interest in the product or brand at that time. It’s called impulse buying, namely the behavior of people who do not plan something for shopping. The act of impulse buying does not always end with satisfaction. Sometimes there is a sense of regret for making a quick decision and wasting money on a product or brand that has been purchased. The purpose of this study was to find out Instagram ads and hedonic shopping motivation on impulse buying through positive emotion. The research method used in this research is a quantitative research method with a causal study. The sampling technique in this research is purposive sampling. The data processing technique in this study uses SEM (Structural Equation Model) analysis based on PLS (Partial Least Square). The Instagram ads variable on the impulse buying variable through the mediation of the positive emotion variable shows that there is no indirect relationship. The hedonic shopping motivation variable on the impulse buying variable through the mediation of the positive emotion variable shows a positive and significant indirect relationship.